Edukasi Perawatan Hipertensi dan Diabetes Melitus di Kelurahan Legok Kota Jambi - Fithriyani, Fithriyani; Putri, Miko Eka (Universitas Baiturrahim, 2024)
Theprevalence of Non-Communicable Diseases has increased, including cancer, stroke,chronic kidney disease, diabetes mellitus, and hypertension. Government efforts have been carried out chronic disease management program (PROLANIS) which is a health service system and a proactive approach that is implemented in an integrated manner. The forms of activities carried out in the PROLANIS program include medical / educational consultation activities, home visits, reminders (evaluation of DM understanding), group activities and health status monitoring. Programs implemented by the government will not run optimally, if people's self-awareness is lacking. One of the efforts that can be done by health workers is education and community empowerment regarding knowledge of hypertension and diabetes mellitus including understanding, causes, signs and symptoms as well as prevention and treatment with complementary therapies. This community service activity will be carried out in Legok Village, Lake Sipin District, Jambi City. The target is around 20 people with educational methods about the treatment of hypertension and diabetes mellitus. The media used in bnetuk powerpoint (PPT) and leaflets of this activity were assisted by one member and 2 students of the Ners Profession. During the assessment of health problems in Legok Village , there were Hypertension and Diabetes Mellitus in almost all RT areas of Legok Village. Healthy living behavior of the community that is still very lacking, especially diet, exercise habits, medication control and lack of health services can be the cause of many hypertensive diseases. The expected outcome of this activity is the increasing understanding of the Legok village community about the treatment of Hypertension and Diabetes Mellitus. This activity was attended by 18 people from Rt 05 Legok Village, cadres and heads of RT along with Ners professional students. The enthusiasm of the community following this activity with many questions asked is hoped to increase people's understanding and be able to apply it in everyday life.